Public healthcare in Nottingham 1750 to 1911 - Bosworth, Ennis C. (1998)
The thesis is a study of the General Hospital, the General Dispensary and the Poor Law system in Nottingham, to evaluate the nature of the public healthcare provision each offered, the way in which they complemented one another and the extent to which they provided comprehensive cover of the healthcare needs of the sick poor and of the pauper sick and geriatric. The types of patients admitted or excluded by each institution and the recommendation systems which operated for the two charities are described. In-, out- and home patient numbers over time are quantified, and comment made in relation to population growth. An analysis and comparison of patient costs is made between the three Nottingham institutions and with comparative data from elsewhere. A major study of the General Hospital finances is made, analysing its management and showing the growing secularisation of funding. The Dispensary finances are also examined. The organisation of the Dispensary, the expansion of its medical districts and medical officers, and its provision of drugs are discussed. The healthcare provision under the Poor Law system is traced from its parochial days until the arrangements made from 1836 when the Union was founded, and the subsequent developments as the Poor Law system had increasingly to address the needs of the pauper sick and geriatric rather than the ablebodied unemployed. Topics treated are accommodation, medical officers and medical districts, drug dispensing and costs, care of imbeciles and those with infectious diseases, vaccination and nursing. The thesis attempts to evaluate the positive aspects of the healthcare provided by each institution while drawing attention to the shortcomings.